A diagnostic study of interannual variability of Indian summer monsoon using outgoing longwave radiation (OLR) data - PAI, D.S. (MAUSAM, 1997)
ABSTRACT. Using the monthly outgoing longwave radiation (OLR) data obtained from NOAA polar orbiting satellites, during the period 1979-92, composite OLR anomalies in respect of good monsoon years (1983 and 1988), bad monsoon years (1982 and 1987 for the case associated with ENSO and 1979 and 1986 separately for the case without ENSO) and normal monsoon years (1980, 1981, 1984, 1985, 1989, 1990, 1991 & 1992) were examined. The computation has been performed over the global tropics (30°N-30°S) bounded between the longitudes 50°E and 130°W (through date line) on 5° longitude × 5° latitude grid. There are significant differences in the spatial distributions of composite OLR anomalies between these four cases from the month of April to September indicating spatial and temporal changes in the organized convective pattern. For the good monsoon years persistent negative anomalies indicating enhanced convective activity were observed over the Indonesian regions, whereas large positive anomalies indicating depressed convective activity were observed over equatorial Pacific just west of date line. During the bad monsoon years above normal convection was observed over Pacific region (ENSO case) and over equatorial Indian Ocean (Non ENSO case). During normal monsoon years the spatial patterns of OLR anomalies were similar to that of good monsoon years, but with weaker anomalies. These observations can be explained through the relative interaction between tropical convergence zone (TCZ) over the Indian sub-continent and that over the north Indian Ocean and Pacific. The eastward shift of the convective activity during El-Nino years can be attributed to shift/reversal of Walker circulation. There are strong signals of OLR anomalies during pre-monsoon months which may be useful in inferring the nature of the subsequent monsoon activity.